Interface-Mediated Twinning-Induced Plasticity in a Fine Hexagonal Microstructure Generated by Additive Manufacturing - Barriobero Vila, Pere (2021)
The grain size is a determinant microstructural feature to enable the activation of deformation twinning in hexagonal close-packed (hcp) metals. Although deformation twinning is one of the most effective mechanisms for improving the strength–ductility trade-off of structural alloys, its activation is reduced with decreasing grain size. This work reports the discovery of the activation of deformation twinning in a fine-grained hcp microstructure by introducing ductile body-centered cubic (bcc) nano-layer interfaces. The fast solidification and cooling conditions of laser-based additive manufacturing are exploited to obtain a fine microstructure that, coupled with an intensified intrinsic heat treatment, permits to generate the bcc nano-layers. In situ high-energy synchrotron X-ray diffraction allows tracking the activation and evolution of mechanical twinning in real-time. The findings obtained show the potential of ductile nano-layering for the novel design of hcp damage tolerant materials with improved life spans.